Antistatic high-temperature-resistant adhesive tape and preparation method thereof
By loading nano silver wires on the peeled montmorillonite surface in antistatic high-temperature resistant tape, forming a conductive network, and combining polyimide and sodium carboxymethylcellulose, the stability of existing tapes in high-temperature environments and The problem of insufficient conductivity has achieved efficient thermal conductivity and anti-static performance improvement.
Patent Information
- Application Number
- CN202411423730.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-03
AI Technical Summary
The existing anti-static high-temperature resistant tapes are insufficient in high-temperature environments, making it difficult to meet the high-standard demand for material performance in the high-tech field.
By evenly dispersing the nano silver wires and loading them on the surface of peeled flake montmorillonite, a continuous conductive network is formed, combining the polyimide substrate layer, antistatic high-temperature resistant layer and adhesive layer to improve thermal conductivity and electrical conductivity. And the heat resistance of the material is enhanced by the action of sodium carboxymethylcellulose and hydrogen bonding.
It significantly improves the thermal conductivity and antistatic properties of the tape, enhances its stability and heat resistance at high temperatures, and meets the high standard demand for material performance in the high-tech field.
Smart Images

Figure BDA0005081575710000091 
Figure BDA0005081575710000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adhesive tapes, and in particular to an antistatic and high temperature resistant adhesive tape and a preparation method thereof. Background Art
[0002] Antistatic and high temperature resistant tape is a special tape designed for extreme environments. It combines two key properties: antistatic and high temperature resistance. This tape is particularly important in the electronics industry because during production and processing, the accumulation of static electricity may damage sensitive microelectronic components and even cause failure of the entire production line. At the same time, many electronic components and materials will encounter high temperature environments during manufacturing or use, which requires the tape to not only prevent static interference, but also be able to withstand high temperatures without failure. Recent research and development have focused on improving the overall performance of tapes, such as enhancing their stability and durability at high temperatures, and improving their antistatic effects. For example, a study proposed an antistatic and high-temperature resistant TPU protective film tape, which includes a transparent base film, an antistatic layer, a polyurethane adhesive layer, and a single-sided release film, and is suitable for the shipment protection and process protection of LCD screens. In addition, there are studies focusing on the development of composite tapes, which provide better temperature resistance and electrostatic protection through a multi-layer structure design. The research background of antistatic and high temperature resistant tapes is closely related to the demand for high-performance materials in modern industry, especially in high-tech fields such as aerospace, military, automobile manufacturing and high-end electronic product assembly, which have extremely high standards and requirements for the performance of materials. With the advancement of technology, the research on these tapes will continue to deepen to meet the ever-changing and upgraded industrial application needs. Summary of the invention
[0003] Technical problem to be solved: The purpose of the present invention is to provide an antistatic and high temperature resistant tape, which can form a continuous conductive network by evenly dispersing and loading nano silver wires on the surface of peeled flaky montmorillonite, which not only maintains the thermal conductivity of the flaky montmorillonite itself, but also increases its conductivity.
[0004] Technical solution: An antistatic and high temperature resistant tape, comprising a substrate layer, an antistatic and high temperature resistant layer and an adhesive layer, wherein the substrate layer is polyimide, and the antistatic and high temperature resistant layer is composed of an adhesive of a nano silver wire-montmorillonite composite material. The method for preparing the above-mentioned antistatic and high temperature resistant tape comprises the following steps: S1. One side of the polyimide membrane is subjected to a hydrophilic treatment; S2. The silver nanowire-montmorillonite composite material is added to water and dispersed evenly to obtain a silver nanowire-montmorillonite composite material dispersion; S3. Add sodium carboxymethyl cellulose to water and mix well to obtain an aqueous solution of sodium carboxymethyl cellulose; S4. The solutions prepared in step S2 and step S3 are mixed in a volume ratio of 1:1, and then coated on the hydrophilic side of the polyimide membrane to obtain an antistatic and high temperature resistant layer; S5. Add cupric chloride dihydrate to water, stir to dissolve, add to water-based epoxy resin, then add triethylenetetramine, mix and stir evenly, and apply to the outside of the antistatic and high temperature resistant layer to obtain an adhesive layer. Preferably, the preparation method of the nano silver wire-montmorillonite composite material comprises the following steps: S11. The montmorillonite was added to anhydrous ethanol to obtain a slurry with a concentration of 5-8wt%, and the slurry was ball-milled at a speed of 300-500rpm for 6-12h. After ball-milling, anhydrous ethanol was further added to the slurry to obtain a slurry with a concentration of 0.5-1wt%, and the slurry was ultrasonically treated for 8-15h, and centrifuged to obtain exfoliated montmorillonite; S12. The exfoliated montmorillonite was added to ethylene glycol, and after ultrasonic dispersion, silver nitrate was added and stirred until completely dissolved to obtain a mixed solution; S13. PVP is added to ethylene glycol, and stirred to mix well to obtain a PVP solution; S14. Add cupric chloride dihydrate to ethylene glycol, stir and mix evenly to obtain a cupric chloride solution. After the cupric chloride solution and the PVP solution are evenly mixed, add them together with the mixed solution of step S12 to the ethylene glycol solvent, react at 150-165°C for 3-5h, and obtain a nano silver wire-montmorillonite composite material. Preferably, the concentration of the nano silver wire-montmorillonite composite material dispersion in step S2 is 0.8-1.5 wt %. Preferably, the concentration of the sodium carboxymethyl cellulose aqueous solution in step S3 is 0.4-0.8 wt %. Preferably, in step S5, the mass ratio of cupric chloride dihydrate, waterborne epoxy resin, triethylenetetramine and water is 1-2:50-70:2-5:30-40. Preferably, in step S12, the concentration of silver nitrate in the mixed solution is 0.5-0.6 mol / L, and the concentration of exfoliated montmorillonite in the mixed solution is 2-4 wt %. Preferably, the concentration of PVP in step S13 is 3-3.6 mol / L. Preferably, the concentration of the cupric chloride solution in step S14 is 7-8 Mmol / L, and the volume ratio of the mixed solution, the PVP solution, the cupric chloride solution and ethylene glycol is 5:5:1:100. Beneficial effects: The antistatic and high temperature resistant adhesive tape of the present invention has the following advantages: 1. In the present invention, the montmorillonite flake structure is peeled off to obtain a single layer of flaky montmorillonite. The peeled flaky montmorillonite can effectively reduce the contact thermal resistance between materials. When coated, the flaky montmorillonite is oriented to form an efficient heat conduction path, thereby improving the thermal conductivity of the overall material; 2. In the present invention, nano silver wires are grown on the surface of the exfoliated flaky montmorillonite. By uniformly dispersing and loading the nano silver wires on the surface of the exfoliated flaky montmorillonite, a continuous conductive network can be formed, which not only maintains the physical and chemical properties of the flaky montmorillonite itself, but also increases its conductivity; 3. The surface of the exfoliated montmorillonite in the present invention has abundant surface hydroxyl polar groups, which are compounded with sodium carboxymethyl cellulose having multiple hydroxyl groups and carboxyl groups. The hydrogen bonding effect between the flaky montmorillonite and the sodium carboxymethyl cellulose and the bonding effect of the sodium carboxymethyl cellulose are utilized to effectively and tightly bond the flaky montmorillonite together. The interface is regulated by ionic crosslinking, thereby increasing the interface interaction between the flaky montmorillonites and improving the heat resistance and antistatic properties of the material. DETAILED DESCRIPTION The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments: Example 1 The preparation method of the antistatic high temperature resistant tape comprises the following steps: S1. One side of the polyimide membrane is subjected to a hydrophilic treatment; S2. The silver nanowire - montmorillonite composite material was added to water and dispersed evenly to obtain a 0.8wt% silver nanowire - montmorillonite composite material dispersion; S3. The sodium carboxymethyl cellulose was added to the water and mixed to obtain a 0.4wt% aqueous solution of sodium carboxymethyl cellulose; S4. The solutions prepared in step S2 and step S3 are mixed in a volume ratio of 1:1, and then coated on the hydrophilic side of the polyimide membrane to obtain an antistatic and high temperature resistant layer; S5. Add cupric chloride dihydrate to water, stir to dissolve, add to water-based epoxy resin, then add triethylenetetramine, cupric chloride dihydrate, water-based epoxy resin, triethylenetetramine and water in a mass ratio of 1:50:2:30, mix and stir evenly, and apply to the outside of the antistatic high temperature resistant layer to obtain an adhesive layer; The method for preparing the nano silver wire-montmorillonite composite material comprises the following steps: S11. The montmorillonite was added to anhydrous ethanol to obtain a slurry with a concentration of 5 wt%, and the slurry was ball-milled at a speed of 500 rpm for 6 h. After ball-milling, anhydrous ethanol was further added to the slurry to obtain a slurry with a concentration of 0.5 wt%, and the slurry was ultrasonically treated for 8 h, and centrifuged to obtain exfoliated montmorillonite; S12. The exfoliated montmorillonite was added to ethylene glycol, and after ultrasonic dispersion, silver nitrate was added and stirred until completely dissolved to obtain a mixed solution, wherein the concentration of silver nitrate in the mixed solution was 0.5 mol / L, and the concentration of the exfoliated montmorillonite in the mixed solution was 4 wt%; S13. PVP was added to ethylene glycol, stirred and mixed to obtain a PVP solution with a concentration of 3 mol / L; S14. Add cupric chloride dihydrate to ethylene glycol, stir and mix evenly to obtain a cupric chloride solution with a concentration of 7 Mmol / L. After the cupric chloride solution and the PVP solution are evenly mixed, add them together with the mixed solution of step S12 to the ethylene glycol solvent. The volume ratio of the mixed solution, PVP solution, cupric chloride solution and ethylene glycol is 5:5:1:100. React at 150°C for 5 hours to obtain a nano silver wire-montmorillonite composite material. Example 2 The preparation method of the antistatic high temperature resistant tape comprises the following steps: S1. One side of the polyimide membrane is subjected to a hydrophilic treatment; S2. The silver nanowire - montmorillonite composite material was added to water and dispersed evenly to obtain a silver nanowire - montmorillonite composite material dispersion having a concentration of 1.5wt%; S3. The sodium carboxymethyl cellulose was added to the water and mixed to obtain a 0.8wt% aqueous solution of sodium carboxymethyl cellulose; S4. The solutions prepared in step S2 and step S3 are mixed in a volume ratio of 1:1, and then coated on the hydrophilic side of the polyimide membrane to obtain an antistatic and high temperature resistant layer; S5. Copper chloride dihydrate is added to water, stirred to dissolve, added to a water-based epoxy resin, and then triethylenetetramine, copper chloride dihydrate, water-based epoxy resin, triethylenetetramine and water in a mass ratio of 2:70:5:40, mixed and stirred evenly, and applied to the outside of the antistatic high temperature resistant layer to obtain an adhesive layer; The method for preparing the nano silver wire-montmorillonite composite material comprises the following steps: S11. The montmorillonite was added to anhydrous ethanol to obtain a slurry with a concentration of 8 wt%, and the slurry was ball-milled at a speed of 300 rpm for 12 h. After the ball-milling, anhydrous ethanol was further added to the slurry to obtain a slurry with a concentration of 1 wt%, and the slurry was ultrasonically treated for 15 h, and centrifuged to obtain exfoliated montmorillonite; S12. The exfoliated montmorillonite was added to ethylene glycol, and after ultrasonic dispersion, silver nitrate was added and stirred until completely dissolved to obtain a mixed solution, wherein the concentration of silver nitrate in the mixed solution was 0.6 mol / L, and the concentration of the exfoliated montmorillonite in the mixed solution was 2 wt%; S13. PVP was added to ethylene glycol, stirred and mixed to obtain a PVP solution with a concentration of 3.6 mol / L; S14. Add cupric chloride dihydrate to ethylene glycol, stir and mix evenly to obtain a cupric chloride solution with a concentration of 8 Mmol / L. After the cupric chloride solution and the PVP solution are evenly mixed, add them together with the mixed solution of step S12 to the ethylene glycol solvent. The volume ratio of the mixed solution, PVP solution, cupric chloride solution and ethylene glycol is 5:5:1:100. React at 165°C for 3 hours to obtain a nano silver wire-montmorillonite composite material. Example 3 The preparation method of the antistatic high temperature resistant tape comprises the following steps: S1. One side of the polyimide membrane is subjected to a hydrophilic treatment; S2. The silver nanowire - montmorillonite composite material is added to water and dispersed evenly to obtain a 1wt% silver nanowire - montmorillonite composite material dispersion; S3. The sodium carboxymethyl cellulose was added to the water and mixed to obtain a 0.7wt% aqueous solution of sodium carboxymethyl cellulose; S4. The solutions prepared in step S2 and step S3 are mixed in a volume ratio of 1:1, and then coated on the hydrophilic side of the polyimide membrane to obtain an antistatic and high temperature resistant layer; S5. Cupric chloride dihydrate is added to water, stirred to dissolve, added to a water-based epoxy resin, and then triethylenetetramine, cupric chloride dihydrate, water-based epoxy resin, triethylenetetramine and water in a mass ratio of 1.2:55:3:32. After mixing and stirring, the mixture is applied to the outside of the antistatic and high temperature resistant layer to obtain an adhesive layer; The method for preparing the nano silver wire-montmorillonite composite material comprises the following steps: S11. The montmorillonite was added to anhydrous ethanol to obtain a slurry with a concentration of 7 wt%, and the slurry was ball-milled at a speed of 300 rpm for 10 h. After ball-milling, anhydrous ethanol was further added to the slurry to obtain a slurry with a concentration of 0.8 wt%, and the slurry was ultrasonically treated for 13 h, and centrifuged to obtain exfoliated montmorillonite; S12. The exfoliated montmorillonite was added to ethylene glycol, and after ultrasonic dispersion, silver nitrate was added and stirred until completely dissolved to obtain a mixed solution, wherein the concentration of silver nitrate in the mixed solution was 0.55 mol / L, and the concentration of the exfoliated montmorillonite in the mixed solution was 2.5 wt%; S13. PVP was added to ethylene glycol, stirred and mixed to obtain a PVP solution with a concentration of 3.6 mol / L; S14. Add cupric chloride dihydrate to ethylene glycol, stir and mix evenly to obtain a cupric chloride solution with a concentration of 8 Mmol / L. After the cupric chloride solution and the PVP solution are evenly mixed, add them together with the mixed solution of step S12 to the ethylene glycol solvent. The volume ratio of the mixed solution, PVP solution, cupric chloride solution and ethylene glycol is 5:5:1:100. React at 160°C for 4 hours to obtain a nano silver wire-montmorillonite composite material. Example 4 The preparation method of the antistatic high temperature resistant tape comprises the following steps: S1. One side of the polyimide membrane is subjected to a hydrophilic treatment; S2. The silver nanowire - montmorillonite composite material was added to water and dispersed evenly to obtain a silver nanowire - montmorillonite composite material dispersion having a concentration of 1.4wt%; S3. The sodium carboxymethyl cellulose was added to the water and mixed to obtain a 0.5wt% aqueous solution of sodium carboxymethyl cellulose; S4. The solutions prepared in step S2 and step S3 are mixed in a volume ratio of 1:1, and then coated on the hydrophilic side of the polyimide membrane to obtain an antistatic and high temperature resistant layer; S5. Copper chloride dihydrate is added to water, stirred to dissolve, added to a water-based epoxy resin, and then triethylenetetramine, copper chloride dihydrate, water-based epoxy resin, triethylenetetramine and water in a mass ratio of 1.8:65:4:37. After mixing and stirring, the mixture is applied to the outside of the antistatic and high temperature resistant layer to obtain an adhesive layer; The method for preparing the nano silver wire-montmorillonite composite material comprises the following steps: S11. The montmorillonite was added to anhydrous ethanol to obtain a slurry with a concentration of 6 wt%, and the slurry was ball-milled at a speed of 500 rpm for 8 h. After ball-milling, anhydrous ethanol was further added to the slurry to obtain a slurry with a concentration of 0.6 wt%, and the slurry was ultrasonically treated for 10 h, and centrifuged to obtain exfoliated montmorillonite; S12. The exfoliated montmorillonite was added to ethylene glycol, and after ultrasonic dispersion, silver nitrate was added and stirred until completely dissolved to obtain a mixed solution, wherein the concentration of silver nitrate in the mixed solution was 0.6 mol / L, and the concentration of the exfoliated montmorillonite in the mixed solution was 3.5 wt%; S13. PVP was added to ethylene glycol, stirred and mixed to obtain a PVP solution with a concentration of 3 mol / L; S14. Add cupric chloride dihydrate to ethylene glycol, stir and mix evenly to obtain a cupric chloride solution with a concentration of 7 Mmol / L. After the cupric chloride solution and the PVP solution are evenly mixed, add them together with the mixed solution of step S12 to the ethylene glycol solvent. The volume ratio of the mixed solution, PVP solution, cupric chloride solution and ethylene glycol is 5:5:1:100. React at 155°C for 5 hours to obtain a nano silver wire-montmorillonite composite material. Example 5 The preparation method of the antistatic high temperature resistant tape comprises the following steps: S1. One side of the polyimide membrane is subjected to a hydrophilic treatment; S2. The silver nanowire - montmorillonite composite material was added to water and dispersed evenly to obtain a silver nanowire - montmorillonite composite material dispersion having a concentration of 1.2wt%; S3. The sodium carboxymethyl cellulose was added to the water and mixed to obtain a 0.6wt% aqueous solution of sodium carboxymethyl cellulose; S4. The solutions prepared in step S2 and step S3 are mixed in a volume ratio of 1:1, and then coated on the hydrophilic side of the polyimide membrane to obtain an antistatic and high temperature resistant layer; S5. Cupric chloride dihydrate is added to water, stirred to dissolve, added to a water-based epoxy resin, and then triethylenetetramine, cupric chloride dihydrate, water-based epoxy resin, triethylenetetramine and water in a mass ratio of 1.5:60:3.5:35. After mixing and stirring, the mixture is applied to the outside of the antistatic and high temperature resistant layer to obtain an adhesive layer; The method for preparing the nano silver wire-montmorillonite composite material comprises the following steps: S11. The montmorillonite was added to anhydrous ethanol to obtain a slurry with a concentration of 6.5 wt%, and the slurry was ball-milled at a speed of 400 rpm for 9 h. After ball-milling, anhydrous ethanol was further added to the slurry to obtain a slurry with a concentration of 0.7 wt%, and the slurry was ultrasonically treated for 12 h, and centrifuged to obtain exfoliated montmorillonite; S12. The exfoliated montmorillonite was added to ethylene glycol, and after ultrasonic dispersion, silver nitrate was added and stirred until completely dissolved to obtain a mixed solution, wherein the concentration of silver nitrate in the mixed solution was 0.55 mol / L, and the concentration of the exfoliated montmorillonite in the mixed solution was 3 wt%; S13. PVP was added to ethylene glycol, stirred and mixed to obtain a PVP solution with a concentration of 3 mol / L; S14. Add cupric chloride dihydrate to ethylene glycol, stir and mix evenly to obtain a cupric chloride solution with a concentration of 7 Mmol / L. After the cupric chloride solution and the PVP solution are evenly mixed, add them together with the mixed solution of step S12 to the ethylene glycol solvent. The volume ratio of the mixed solution, PVP solution, cupric chloride solution and ethylene glycol is 5:5:1:100. React at 160°C for 4.5 hours to obtain a nano silver wire-montmorillonite composite material. Comparative Example 1 The preparation method of the antistatic high temperature resistant tape comprises the following steps: S1. One side of the polyimide membrane is subjected to a hydrophilic treatment; S2. The silver nanowire - montmorillonite composite material was added to water and dispersed evenly to obtain a silver nanowire - montmorillonite composite material dispersion having a concentration of 1.2wt%; S3. The sodium carboxymethyl cellulose was added to the water and mixed to obtain a 0.6wt% aqueous solution of sodium carboxymethyl cellulose; S4. The solutions prepared in step S2 and step S3 are mixed in a volume ratio of 1:1, and then coated on the hydrophilic side of the polyimide membrane to obtain an antistatic and high temperature resistant layer; S5. Cupric chloride dihydrate is added to water, stirred to dissolve, added to a water-based epoxy resin, and then triethylenetetramine, cupric chloride dihydrate, water-based epoxy resin, triethylenetetramine and water in a mass ratio of 1.5:60:3.5:35. After mixing and stirring, the mixture is applied to the outside of the antistatic and high temperature resistant layer to obtain an adhesive layer; The method for preparing the nano silver wire-montmorillonite composite material comprises the following steps: S11. The montmorillonite was added to ethylene glycol, and after being uniformly dispersed by ultrasonication, silver nitrate was added and stirred until completely dissolved to obtain a mixed solution, wherein the concentration of silver nitrate in the mixed solution was 0.55 mol / L, and the concentration of montmorillonite in the mixed solution was 3 wt%; S13. PVP was added to ethylene glycol, stirred and mixed to obtain a PVP solution with a concentration of 3 mol / L; S14. Add cupric chloride dihydrate to ethylene glycol, stir and mix evenly to obtain a cupric chloride solution with a concentration of 7 Mmol / L. After the cupric chloride solution and the PVP solution are evenly mixed, add them together with the mixed solution of step S12 to the ethylene glycol solvent. The volume ratio of the mixed solution, PVP solution, cupric chloride solution and ethylene glycol is 5:5:1:100. React at 160°C for 4.5 hours to obtain a nano silver wire-montmorillonite composite material. Comparative Example 2 The preparation method of the antistatic high temperature resistant tape comprises the following steps: S1. One side of the polyimide membrane is subjected to a hydrophilic treatment; S2. The silver nanowire - montmorillonite composite material was added to water and dispersed evenly to obtain a silver nanowire - montmorillonite composite material dispersion having a concentration of 1.2wt%; S3. The sodium carboxymethyl cellulose was added to the water and mixed to obtain a 0.6wt% aqueous solution of sodium carboxymethyl cellulose; S4. The solutions prepared in step S2 and step S3 are mixed in a volume ratio of 1:1, and then coated on the hydrophilic side of the polyimide membrane to obtain an antistatic and high temperature resistant layer; S5. The water, water-based epoxy resin and triethylenetetramine are added, and the mass ratio of water-based epoxy resin, triethylenetetramine and water is 60:3.5:35, mixed and stirred evenly, and then coated on the outside of the antistatic high temperature resistant layer to obtain an adhesive layer; The method for preparing the nano silver wire-montmorillonite composite material comprises the following steps: S11. The montmorillonite was added to anhydrous ethanol to obtain a slurry with a concentration of 6.5 wt%, and the slurry was ball-milled at a speed of 400 rpm for 9 h. After ball-milling, anhydrous ethanol was further added to the slurry to obtain a slurry with a concentration of 0.7 wt%, and the slurry was ultrasonically treated for 12 h, and centrifuged to obtain exfoliated montmorillonite; S12. The exfoliated montmorillonite was added to ethylene glycol, and after ultrasonic dispersion, silver nitrate was added and stirred until completely dissolved to obtain a mixed solution, wherein the concentration of silver nitrate in the mixed solution was 0.55 mol / L, and the concentration of the exfoliated montmorillonite in the mixed solution was 3 wt%; S13. PVP was added to ethylene glycol, stirred and mixed to obtain a PVP solution with a concentration of 3 mol / L; S14. Add cupric chloride dihydrate to ethylene glycol, stir and mix evenly to obtain a cupric chloride solution with a concentration of 7 Mmol / L. After the cupric chloride solution and the PVP solution are evenly mixed, add them together with the mixed solution of step S12 to the ethylene glycol solvent. The volume ratio of the mixed solution, PVP solution, cupric chloride solution and ethylene glycol is 5:5:1:100. React at 160°C for 4.5 hours to obtain a nano silver wire-montmorillonite composite material. Comparative Example 3 The preparation method of the antistatic high temperature resistant tape comprises the following steps: S1. One side of the polyimide membrane is subjected to a hydrophilic treatment; S2. The nano-silver powder and montmorillonite were added to water, the mass ratio of the nano-silver powder, montmorillonite and water was 1.2:1:50, and ultrasonically dispersed to obtain a mixed solution; S3. The sodium carboxymethyl cellulose was added to the water and mixed to obtain a 0.6wt% aqueous solution of sodium carboxymethyl cellulose; S4. The solutions prepared in step S2 and step S3 are mixed in a volume ratio of 1:1, and then coated on the hydrophilic side of the polyimide membrane to obtain an antistatic and high temperature resistant layer; S5. Add cupric chloride dihydrate to water, stir to dissolve, add to water-based epoxy resin, then add triethylenetetramine, cupric chloride dihydrate, water-based epoxy resin, triethylenetetramine and water in a mass ratio of 1.5:60:3.5:35, mix and stir evenly, and apply to the outside of the antistatic and high temperature resistant layer to obtain an adhesive layer. Comparative Example 4 The preparation method of the antistatic high temperature resistant tape comprises the following steps: S1. One side of the polyimide membrane is subjected to a hydrophilic treatment; S2. The silver nanowire - montmorillonite composite material was added to water and dispersed evenly to obtain a silver nanowire - montmorillonite composite material dispersion having a concentration of 1.2wt%; S3. The sodium carboxymethyl cellulose was added to the water and mixed to obtain a 0.6wt% aqueous solution of sodium carboxymethyl cellulose; S4. The solutions prepared in step S2 and step S3 are mixed in a volume ratio of 1:1, and then coated on the hydrophilic side of the polyimide membrane to obtain an antistatic and high temperature resistant layer; S5. Cupric chloride dihydrate is added to water, stirred to dissolve, added to a water-based epoxy resin, and then triethylenetetramine, cupric chloride dihydrate, water-based epoxy resin, triethylenetetramine and water in a mass ratio of 1.5:60:3.5:35. After mixing and stirring, the mixture is applied to the outside of the antistatic and high temperature resistant layer to obtain an adhesive layer; The method for preparing the nano silver wire-montmorillonite composite material comprises the following steps: S11. The montmorillonite was added to anhydrous ethanol to obtain a slurry with a concentration of 6.5 wt%, and the slurry was ball-milled at a speed of 400 rpm for 9 h. After ball-milling, anhydrous ethanol was further added to the slurry to obtain a slurry with a concentration of 0.7 wt%, and the slurry was ultrasonically treated for 12 h, and centrifuged to obtain exfoliated montmorillonite; S12. The exfoliated montmorillonite was added to ethylene glycol, and after ultrasonic dispersion, silver nitrate was added and stirred until completely dissolved to obtain a mixed solution, wherein the concentration of silver nitrate in the mixed solution was 0.55 mol / L, and the concentration of the exfoliated montmorillonite in the mixed solution was 3 wt%; S13. PVP was added to ethylene glycol, stirred and mixed to obtain a PVP solution with a concentration of 3 mol / L; S14. Add the PVP solution and the mixed solution of step S12 into the ethylene glycol solvent, the volume ratio of the mixed solution, the PVP solution, and the ethylene glycol is 5:5:100, and react at 160° C. for 4.5 hours to obtain a nano silver wire-montmorillonite composite material. Performance test: Wrap the test sample loosely with insulation material (such as asbestos cloth) (without affecting the tensile value) and heat it in an oven at 150°C for 30 minutes. Take it out of the oven and quickly (within 15 seconds) measure the bonding shear strength; the square resistance of the tape is measured using a four-probe square resistance meter. Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. An antistatic and high temperature resistant tape, characterized in that: The antistatic and high temperature resistant tape comprises a substrate layer, an antistatic and high temperature resistant layer and an adhesive layer. The substrate layer is polyimide, and the antistatic and high temperature resistant layer is composed of an adhesive of a nano silver wire-montmorillonite composite material.
2. The method for preparing the antistatic and high temperature resistant tape according to claim 1, characterized in that: The following steps are involved: S1. One side of the polyimide membrane is subjected to a hydrophilic treatment; S2. The silver nanowire-montmorillonite composite material is added to water and dispersed evenly to obtain a silver nanowire-montmorillonite composite material dispersion; S3. Add sodium carboxymethyl cellulose to water and mix well to obtain an aqueous solution of sodium carboxymethyl cellulose; S4. The solutions prepared in step S2 and step S3 are mixed in a volume ratio of 1:1, and then coated on the hydrophilic side of the polyimide membrane to obtain an antistatic and high temperature resistant layer; S5. Add cupric chloride dihydrate to water, stir to dissolve, add to water-based epoxy resin, then add triethylenetetramine, mix and stir evenly, and apply to the outside of the antistatic and high temperature resistant layer to obtain an adhesive layer.
3. The method for preparing the antistatic and high temperature resistant tape according to claim 2, characterized in that: The preparation method of the nano silver wire-montmorillonite composite material comprises the following steps: S11. The montmorillonite was added to anhydrous ethanol to obtain a slurry with a concentration of 5-8wt%, and the slurry was ball-milled at a speed of 300-500rpm for 6-12h. After ball-milling, anhydrous ethanol was further added to the slurry to obtain a slurry with a concentration of 0.5-1wt%, and the slurry was ultrasonically treated for 8-15h, and centrifuged to obtain exfoliated montmorillonite; S12. The exfoliated montmorillonite was added to ethylene glycol, and after ultrasonic dispersion, silver nitrate was added and stirred until completely dissolved to obtain a mixed solution; S13. PVP is added to ethylene glycol, and stirred to mix well to obtain a PVP solution; S14. Add cupric chloride dihydrate to ethylene glycol, stir and mix evenly to obtain a cupric chloride solution. After the cupric chloride solution and the PVP solution are evenly mixed, add them together with the mixed solution of step S12 to the ethylene glycol solvent, react at 150-165°C for 3-5h, and obtain a nano silver wire-montmorillonite composite material.
4. The method for preparing the antistatic and high temperature resistant tape according to claim 2, characterized in that: The concentration of the nano silver wire-montmorillonite composite material dispersion in step S2 is 0.8-1.5 wt %.
5. The method for preparing the antistatic and high temperature resistant tape according to claim 2, characterized in that: The concentration of the sodium carboxymethylcellulose aqueous solution in step S3 is 0.4-0.8 wt %.
6. The method for preparing the antistatic and high temperature resistant tape according to claim 2, characterized in that: In the step S5, the mass ratio of cupric chloride dihydrate, waterborne epoxy resin, triethylenetetramine and water is 1-2:50-70:2-5:30-40.
7. The method for preparing the antistatic and high temperature resistant tape according to claim 3, characterized in that: In step S12, the concentration of silver nitrate in the mixed solution is 0.5-0.6 mol / L, and the concentration of exfoliated montmorillonite in the mixed solution is 2-4 wt %.
8. The method for preparing the antistatic and high temperature resistant tape according to claim 3, characterized in that: The concentration of PVP in step S13 is 3-3.6 mol / L.
9. The method for preparing the antistatic and high temperature resistant tape according to claim 3, characterized in that: The concentration of the cupric chloride solution in step S14 is 7-8 Mmol / L, and the volume ratio of the mixed solution, the PVP solution, the cupric chloride solution and ethylene glycol is 5:5:1:100.